2018
DOI: 10.1136/bjophthalmol-2018-312277
|View full text |Cite
|
Sign up to set email alerts
|

Ocular preservation with neoadjuvant vismodegib in patients with locally advanced periocular basal cell carcinoma

Abstract: Neoadjuvant vismodegib for locally advanced (T4) periocular BCC enabled an eye-sparing surgery in all patients in our cohort. Prolonged treatment was well tolerated by most patients. Over half of patients achieved a complete response with no residual microscopic disease. Careful long-term follow-up is needed to confirm long-term disease-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 20 publications
6
69
1
Order By: Relevance
“…The interventions were successful with disease-free margins, and the patients are currently in follow-up without disease recurrence. A neoadjuvant approach with HPIs has already been reported previously 16,17,18 . In this setting, the use of sonidegib may be of interest since AEs seem to appear slightly later than with vismodegib 6 .…”
Section: Discussionmentioning
confidence: 95%
“…The interventions were successful with disease-free margins, and the patients are currently in follow-up without disease recurrence. A neoadjuvant approach with HPIs has already been reported previously 16,17,18 . In this setting, the use of sonidegib may be of interest since AEs seem to appear slightly later than with vismodegib 6 .…”
Section: Discussionmentioning
confidence: 95%
“…The pivotal study, a prospective nonrandomized clinical trial, revealed a 43% response rate among patients with locally advanced BCC and 30% response rate among patients with metastatic BCC, with a median duration of response of 7.6 months [ 8 ]. Prospective trials have assessed vismodegib as a neoadjuvant in a variety of body locations [ 17 , 18 , 19 ], and several case studies have highlighted the efficacy of vismodegib for preserving vision in patients with orbital BCC [ 20 , 21 , 22 , 23 , 24 , 25 ]. More recently, post hoc prospective analysis of the multisite multicountry Safety Events in Vismodegib study data showed either complete or partial response to vismodegib in 67% of patients [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained by the lack of clear guidelines for the definition of remission. Several studies were based on a clinical examination (mainly based on the RECIST criteria [ 15 , 17 ]), whereas other studies were based on a systematic surgical biopsy [ 16 ]. Of course, the histological analysis remains the gold standard, and the benefit/risk ratio and economic balance should be carefully considered for each patient.…”
Section: Second Step Towards Eye-sparing Strategies: Use Of Targeted Therapies and Immunotherapiesmentioning
confidence: 99%